QUALITY ANALYSIS OF VALUE ADDED LASSI (International Journal of Food and Nutritional Sciences, 2022)
Lassi is a popular traditional yogurt-based drink from the Indian Subcontinent. It is a blend of yogurt, water, spices and sometimes fruits1. In the present study lassi was incorporated with carrot, beetroot and mint purees to increase the nutritional properties, flavour, taste and colour. Nutrients like vitamin – A, vitamin – C, potassium, iron and dietary fiber are higher in purees incorporated lassi while compared with standard lassi. Physicochemical properties like pH, total soluble solids, titrable acidity and ash content were analysed. The incorporated lassi were organoleptically evaluated by 25 semi trained panel members for appearance, colour, flavor, taste, consistency and overall acceptability by using nine-point hedonic rating test. Microbial analysis was done on 4th day in the lassi kept under refrigeration. Cost for preparing 100ml standard lassi and purees incorporated lassi were calculated and also compared with other brands. On the basis of findings, it was concluded that 30% carrot puree incorporated lassi, 20% beetroot puree incorporated lassi and 15% mint puree incorporated lassi were highly acceptable among the other variations and standard lassi. The cost of purees incorporated lassi was found to be affordable.